Controllable preparation of uniform polystyrene nanospheres with premix membrane emulsification. Issue 3 (27th November 2012) - Liu, Zhendong; Lu, Yangcheng; Zhang, Man; Wan, Weiming; Luo, Guangsheng
Abstract The expansion of polymer nanosphere applications requires facile and versatile preparation techniques. In this study, combining circled premix membrane emulsification and thermally initiated miniemulsion polymerization, we developed a new strategy for preparing uniform polystyrene nanospheres within a duration as short as 1 h. The size of the nanospheres, ranging from 40 to 120 nm, was dependent on the premix membrane emulsification cycle number, the transmembrane flow rate, and the membrane pore size; this was almost consistent with characterizations of droplet size evolution. The coefficient of variation, around 15%, indicated that the size distribution of the nanospheres was still narrow, even as the monomer‐to‐water ratio was as high as 0.2. This method may be competitive for further applications because of its high production efficiency and low system requirements. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013